Post-mining Land of Limestone Quarries for Sengon Plants in PT Semen Baturaja (Persero) Tbk - regi suhada pujakesuma; Restu Juniah; Harminuke Eko Handayani (Research Centre of Inorganic Materials and Complexs, 2018)
Limestone mining in PT Semen Baturaja mine mining materials in the form of limestone. Limestone is the material needed to make cement. Open mining activities at the final stage will leave ex-mining land. Ex-mine land in the PT Semen Baturaja reclamation area has been planned for revegetation of sengon seedlings. The research was conducted to examine economically post-mining land of limestone mines for sengon plantations. The initial baseline studied in the study area includes climate, space and geological conditions, and vegetation. Some plants in the study area include sengon, cypress, and guava. The results showed that the use of limestone quarry land for sengon plants had met economically. The results of the study are expected to be utilized by stakeholders, academics, practitioners, researchers, mining associations and the environment.